1999
DOI: 10.3168/jds.s0022-0302(99)75348-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extrusion of Grain and Feeding Frequency on Rumen Fermentation, Nutrient Digestibility, and Milk Yield and Composition in Dairy Cows

Abstract: The effect of corn extrusion and feeding frequency on ruminal and postruminal digestibility and milk yield was studied in cows fed a high concentrate diet. Four Israeli Holstein cows fitted with rumen and abomasal cannulas were used. The experiment was arranged as a 2 x 2 factorial design, with two diets and two feeding frequencies (two or four meals per day). One diet contained 40% ground corn. In the second diet, half of the ground corn was replaced with extruded corn. Feeding cows the extruded versus ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
100
7
10

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(136 citation statements)
references
References 24 publications
19
100
7
10
Order By: Relevance
“…Rumen bacteria can utilize more NH 3 nitrogen for protein synthesis in the presence of readily available energy (NRC, 2001). As grinding increases fermentability of grain starch, the utilization of NH 3 nitrogen for microbial protein synthesis could have been higher in ground diets compared with rolled diets resulting in lower NH 3 nitrogen in ground diets than in rolled diets (Meyer et al, 1967;Shabi et al, 1999). The shift in the end products of fermentation observed in our study highlights the fact that grain source and processing affects rumen availability of carbohydrates and protein, which in turn, affects the end products of digestion (Dijkstra, 1994).…”
Section: Rumen Fermentationmentioning
confidence: 62%
“…Rumen bacteria can utilize more NH 3 nitrogen for protein synthesis in the presence of readily available energy (NRC, 2001). As grinding increases fermentability of grain starch, the utilization of NH 3 nitrogen for microbial protein synthesis could have been higher in ground diets compared with rolled diets resulting in lower NH 3 nitrogen in ground diets than in rolled diets (Meyer et al, 1967;Shabi et al, 1999). The shift in the end products of fermentation observed in our study highlights the fact that grain source and processing affects rumen availability of carbohydrates and protein, which in turn, affects the end products of digestion (Dijkstra, 1994).…”
Section: Rumen Fermentationmentioning
confidence: 62%
“…This effect is associated with the lowering of methanogens as a result of high fluctuations in ruminal pH, since low meal frequencies increase diurnal fluctuations in ruminal pH that can be inhibitory to methanogens (Sutton et al 1986;Shabi et al 1999). On the other hand, more frequent feeding was shown to increase the acetate: propionate ratio (Sutton et al 1986;French and Kennelly 1990).…”
Section: Feeding Frequencymentioning
confidence: 99%
“…Previous studies indicated that grain processing level influenced rumen NH 3 -N concentration (Lesmeister and Heinrichs, 2004). Shabi et al (1999) reported that as grinding increases fermentability of grain starch in the rumen, the utilization of NH 3 -N for microbial protein synthesis could have been greater in ground grains as compared to rolled grains resulting in lower NH 3 -N in ground diets than in rolled diets. Knowing the differences in particle size between rolled and ground diets and the expected differences in rates of starch fermentation between barley and maize, we hypothesized that rumen NH 3 -N levels in calves fed dry-rolled diets (maize or barley) would be lower in comparison to those fed ground diets (barley or maize).…”
Section: Discussionmentioning
confidence: 99%